Teacher reaction to 1989 curriculum change in Newfoundland and Labrador elementary core French - Warr, Harold J., 1955- (1995)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1995. Education Bibliography: leaves 63-71. The aim of this study was to determine teacher reaction to a curriculum change in elementary core French. In most cases a particular curriculum is changed and a new one implemented without a formal evaluation of whether or not the implementation was successful. As a result of informal discussions with teachers it was learned that the change in curriculum in elementary core French was successful, but that there were some difficulties with the new program. This study is, therefore, an example of how to evaluate a program that has already been implemented. -- In order to determine exactly the successes and difficulties with the new program, a survey was developed using the new elementary core French curriculum guide as a source for the questions to be posed. The survey was composed of two sections. The first consisted of fifteen items and asked teachers for demographic information. The second required teachers to rate on a scale of five to zero forty-four statements which were based on program objectives. The survey was administered to all teachers of elementary core French in schools operated by the Pentecostal Assemblies Board of Education. The Pentecostal Assemblies Board of Education is a provincial board with schools representative of the types that are found in Newfoundland and Labrador. -- Out of a total of forty-one surveys sent out, there were thirty-five completed and returned. Although a descriptive study, SPSS, a comprehensive, integrated system for statistical analysis, was used to determine frequency distributions of the variables on which the survey was based. As well, Pearson correlation coefficients were calculated to determine what linear relationships exist between the variables. -- As a result of this survey analysis it was learned that teachers are favourably impressed with the curriculum change. However, they feel that there are some difficulties with the authorized resource at the grade six level. Teachers have stated that the grade six resource does not provide for continuity from grade five to grade six and that many of the suggested activities in the grade six resource are not suitable for students who have previously studied core French for only two years. -- The challenge facing teachers who use this curriculum is to make certain that the objectives outlined in the curriculum guide are met even if it means considerable adaptation of the resource that has been authorized for use in grade six. If the resource-based learning and teaching philosophy of the Department of Education is followed by the teachers, students should have a successful experience in elementary core French no matter what resources are used.